Facile Microwave-assisted Synthesis Manganese Doped Zinc Sulfide Nanoparticles. Issue 1 (December 2018) - Sousa, David; Alves, Luís; Marques, Ana; Gaspar, Guilherme; Lima, João; Ferreira, Isabel
Abstract Undoped and manganese doped zinc sulfide nanoparticles were produced by a fast, one-step and two-component microwave-assisted synthesis method. The solid phase retains around 78% of the initial Mn concentration, as revealed by Particle Induced X-ray Emission analysis. X-ray diffraction patterns confirmed zinc blende structure and in the transmission electron microscopy images, nanoparticles with triangular prism and cube shapes were observed, respectively with an average particle size around 7 nm and 13 nm. Dried powders of zinc sulfide nanoparticles, doped with 0.1 mol% and 0.7 mol% of Mn ions, show highest brilliance of luminescence under UV light. Increasing dopant levels resulted in a diminishing emission that vanishes above 4% of dopant concentration. The synthesis of ZnS was monitored and two main events were detected, one at 145 °C corresponding to the sol-gel phase formation and another after ~3 min at 300 °C where the precipitation of the zinc sulfide nanoparticles occurs.